SYSTEMATIC JOURNAL REVIEW (SJR): CURRENT MANAGEMENT OF PREURICULAR FISTULA WITH AND WITHOUT ABSCESS - Christanto, Antonius (HEARTY, 2025)
Preauricular fistula is a congenital anomaly that may lead to recurrent infections and abscess formation. Its management typically involves a combination of antibiotic therapy and surgical interventions, such as tract excision or a supra-auricular approach, which have been shown to reduce recurrence rates. However, a standardized clinical consensus regarding the optimal treatment method remains lacking. This systematic review aims to identify the most effective diagnostic and therapeutic strategies based on the latest scientific evidence to assist clinicians in managing these cases optimally. This study employed the Systematic Journal Review (SJR) method to critically appraise the scientific literature concerning the management of preauricular fistulas, both with and without abscess formation. A structured approach following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines was used, with data sourced from reputable databases including PubMed, Scopus, ScienceDirect, and Google Scholar. Articles were selected based on stringent inclusion and exclusion criteria through a stepwise process, from keyword search to full-text appraisal, yielding 27 eligible studies for comprehensive analysis. Findings from this review emphasize the importance of complete fistula tract excision to prevent recurrence, highlighting various surgical techniques such as hidden incisions and local skin flaps that enhance both aesthetic and clinical outcomes. Standardized procedures, including the use of magnification and methylene blue dye, are also considered essential to ensure complete excision. Nevertheless, limitations such as study heterogeneity, small sample sizes, and lack of controlled trials restrict the strength of conclusions and meta-analytic synthesis. Therefore, further research with robust design, larger sample sizes, standardized protocols, and the inclusion of negative findings is necessary to strengthen the evidence base for preauricular fistula management.